Análise perceptiva dos resultados do processo de aprendizagem dos alunos do fundamental I, participantes de atividades de corrida de orientação no contexto escolar - Freitas, Nairana Cristina Santos (2023)
One of the important factors of Physical Education is the search for transformation, associated with an innovative pedagogical practice, which requires initiatives for a continuous learning process. Therefore, the objective of this study was to investigate the educational process of participants in Physical Education classes in Elementary School I through the orienteering race. Aquantitative methodology was used, with qualitative analyzes of action research aimedat identifying the quality of teaching, in an action that involved researchers and interested groups. Physical adventure activities in nature have been promising in the educational space, due to their pedagogical potential and their interdisciplinary character, which has contributed to building knowledge and creating bonds. The objective of the orienteering race is to travel in unknown terrain, using equipment suchas a map and a compass, in search of the control points in the determined route, the orienteer's objective is to find the control points with greater speed and skill. Given these specific characteristics of the modality, it is observed that its practice requires the participant to be able to solve problems, as well as quick thinking for decision making, providing self-control, and stimulation of reasoning in challenges practiced in a natural environment. The results showed that the orienteering sport developed in the school environment can be considered an excellent pedagogical tool, with new insertion possibilities, which have provided a beneficial growth for students and the school community, providing quality of teaching and helping in the teaching learning process.